CENTRAL ASIA IN INDIA’S ENERGY QUEST - PRADHAN, Ramakrushna; ZHOLDASBEKOVA, Akbota; Ali AVCU, Seyit; LAPENKO, Marina (CENTRAL ASIA AND THE CAUCASUS, 2019)
Central Asia has recently assumed a new and prominent role in global politics due to its enormous untapped base of hydrocarbon resources and massive deposits of uranium. The emergence of the region as an energy-producing center, highlighted by recent geological surveys, has undoubtedly invited global competition. This has led to a struggle for resources between major players such as the U.S., China, Europe, and others. India, a country with substantial energy consumption similar to China, has also been seeking regional opportunities to meet its energy needs. Central Asia is a viable option for India from the perspectives of supply security and cost-benefit analysis, offering an alternative to the hostile and unstable Middle East. Additionally, the hydrocarbons from Central Asia are of high quality, and the producing countries consume minimal amounts themselves.In light of these circumstances, the article attempts to understand India’s important energy quest in the region and examines how Central Asian energy is relevant to India’s energy security concerns. It employs comparative analysis of the energy potential of the Central Asian countries and adheres to the viewpoint that India is actively involved in the oil politics of Central Asia. Meanwhile, it suggests that India should seriously consider establishing strong political ties with the countries of the region if it wishes to play a major role in the region's energy sectors. India needs strategic thinking in this respect and must prioritize the region in its foreign policy doctrine. In the energy sector, India needs a concrete strategy, particularly in light of the tough competition with China in the long term. New Delhi must make prompt and tough decisions if it is serious about the resource struggle in Central Asia.